A killer in the family : a novel - Ahmad, A. X. (Henry Holt and Company, 2026)
"Ali Azeem, a naive Muslim bachelor from Mumbai, thinks he has hit the jackpot when he agrees to an arranged marriage with Maryam Khan, daughter of Abbas Khan, a self-made real-estate tycoon and one of the richest men in New York. Moving with her to the United States, Ali quickly enters an intoxicating, Gatsbyesque world of supertall skyscrapers, sumptuous clothing, and helicopter rides to the Hamptons. However, shortly after the newlyweds move into one of the city's most luxurious apartments, Maryam's older sister, Farhan, tells Ali that beneath her father's success lies sinister deeds. But can Farhan be trusted? She is a rebellious outsider and, according to Maryam, an unstable liar. Plus, as the newly minted husband of Abbas's favorite daughter, Ali has an open invitation to join Tiger Corp., the family's business empire. Before he commits, Ali launches his own investigation to determine who the Khans really are: the embodiment of the American dream--or cutthroat one-percenters out for themselves? As he closes in on the truth, Ali must ask himself if he can pay the price unimaginable wealth demands"-- Provided by publisher.